Blended SPOC Teaching and Learning Model for Computer Programming Course: Insights and Defeating Challenges - Gupta, Vishal (Proceedings of IEEE International Conference on Teaching, Assessment, and Learning for Engineering (Online), 2020)
To expose all budding engineers to the world of programming, generally, Computer Programming is a first-year compulsory course across all Engineering disciplines. While this course has been taught for a long in the university whose case study is presented here, the following challenges were faced over the past few years: (a) University expended itself from one campus to four geographically distant campuses. (b) Many (but not all) students now are already exposed to this programming subject at their respective 10+2 level, which poses a challenge to an instructor. (c) The focus of this course is on "Programming" and C-language is a tool to learn it, but often students feel the reverse. (e) Although all campuses shared a common handout that standardized the breadth coverage of this course, in-depth coverage could not be standardized. To overcome these problems, the university changed the teaching model of the course to a flipped classroom-based blended SPOC (Small Private Online Course) learning model. This paper shares the insights and experience of successive change in pedagogy over four years and relates it with intrinsic motivation vs. extrinsic motivation, standardizing in-depth coverage of any course across geographically distant campuses, and getting closer towards achieving the learning objectives.